Bermudagrass for Florida Lawns - Laurie E. Trenholm; Marco Schiavon; J. Bryan Unruh; Travis W. Shaddox (EDIS)
Bermudagrasses are among the most widely used warm-season grasses. Improved, fine-textured bermudagrasses are used throughout the South on golf courses, athletic fields, and in high-profile residential and commercial landscapes where a fine-textured, dense ground cover is desired. This publication reviews current cultivars available in Florida and best management practices for maintaining bermudagrass lawns in Florida. Minor revision by L. Trenholm, M. Schiavon, J.B. Unruh, and T. Shaddox; 5 pp. https://edis.ifas.ufl.edu/lh007